2008
DOI: 10.1128/jvi.00935-08
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor 3 Has a Protective Role against West Nile Virus Infection

Abstract: Protection against West Nile virus (WNV) infection requires rapid viralRecent studies have begun to delineate the molecular mechanisms that regulate alpha interferon (IFN-␣) and IFN-␤ induction after infection by RNA and DNA viruses (reviewed in references 13, 24, 25, and 57). Pattern recognition receptors (PRR) sense conserved structural microbial elements identified as pathogen-associated molecular patterns. PRR involved in the recognition of RNA viruses can be divided into two classes. Toll-like receptors (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
291
3
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 303 publications
(315 citation statements)
references
References 61 publications
14
291
3
1
Order By: Relevance
“…Yet, studies in mice and humans have indicated that TLR3 may act as a double-edge sword during viral infection and subsequent pathology. In fact, Tlr3 2/2 mice display increased mortality after infection with murine CMV, encephalomyocarditis virus, coxsackievirus B, and intracranially inoculated West Nile virus (WNV) (17)(18)(19)(20). Conversely, animals lacking a functional Tlr3 gene display milder pathology when challenged with phlebovirus, influenza A virus, and i.p.-administered WNV (21-23).…”
Section: Discussionmentioning
confidence: 99%
“…Yet, studies in mice and humans have indicated that TLR3 may act as a double-edge sword during viral infection and subsequent pathology. In fact, Tlr3 2/2 mice display increased mortality after infection with murine CMV, encephalomyocarditis virus, coxsackievirus B, and intracranially inoculated West Nile virus (WNV) (17)(18)(19)(20). Conversely, animals lacking a functional Tlr3 gene display milder pathology when challenged with phlebovirus, influenza A virus, and i.p.-administered WNV (21-23).…”
Section: Discussionmentioning
confidence: 99%
“…TLR3 2/2 or TICAM-1 2/2 mice became more resistant to WNV infection than did WT mice (52). Compared to these earlier results, a recent report showed that lack of TLR3 enhances WNV mortality and increases viral burden in the brain (53). TNF-a and IL-6 are induced for inflammation, and high IL-10 production causes an increase of mortality in WNV-infected mice (54).…”
Section: Discussionmentioning
confidence: 80%
“…TNF-a and IL-6 are induced for inflammation, and high IL-10 production causes an increase of mortality in WNV-infected mice (54). TICAM-1 signaling is undoubtedly involved in the modulation of these cytokine productions and WNV replication in the nervous system (53,54). In patients with herpes simplex encephalitis, functional deficiency of TLR3 or TICAM-1 is a critical factor for disease progression (55).…”
Section: Discussionmentioning
confidence: 99%
“…This study also linked TLR3 to a TNF-α-mediated reduction in blood-brain barrier (BBB) integrity upon WNV infection. However, a subsequent study reported that TLR3 deficiency resulted in enhanced WNV replication in primary cortical neurons, and that viral replication was actually increased in the brain and spinal chord of Tlr3 -/-mice [31]. The contrasting conclusions from these studies [30,31] may reflect differences in viral doses and/or routes of administration used.…”
Section: Role Of Tlr3 In Host Defencementioning
confidence: 77%
“…Additionally, children with a particular TLR3 polymorphism (rs5743313/CT) have an increased risk of pneumonia caused by the pandemic IAV/H1N1 (2009) [29]. Complex roles for TLR3 in host protection versus immunopathology have also reported in other viral infection models, for example West Nile virus (WNV) [30,31]. An initial study showed that Tlr3 -/-mice were protected from WNV-induced encephalitis, because of reduced viral entry into the central nervous system [30].…”
Section: Role Of Tlr3 In Host Defencementioning
confidence: 99%